Pentas Opera Tokong Cheng Hoon Teng, No. 25, Jalan Tokong, 75200, Melaka [technical drawing] - Chua, Chee Yong; Cheah, Kim Heng; Muzamir Izham Mustafa; Sharil Nizam Kamaruddin; Chan, Pau Moy; Teo, Lay Teng (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2002